Indonesian Stock Market Reaction to U.S. Liberation Day Tariff on Export Firms - Arya Nurhasan; Retno Yuni Nur Susilowati (Studi Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study examines the reaction of Indonesia's capital market to the U.S. Liberation Day Tariff announcement on April 2, 2025, focusing on export-exposed firms listed on the Indonesia Stock Exchange (IDX). Methodology: An event study is applied across 62 IDX-listed firms over a 21-trading-day window, analyzing abnormal returns and trading volume activity using the market-adjusted model and Wilcoxon signed rank test. Results: The tariff announcement produced a significant negative difference in abnormal returns, with investors perceiving the policy as bad news for export-oriented firms. The average abnormal return was partially significant, with an immediate event-day response and persistent negative reactions post-announcement. Trading volume activity showed no significant difference, reflecting the caution of investors. Conclusions: Price movements support semi-strong market efficiency, while the absence of a volume response confirms that price and volume reactions do not always co-move under the same informational events. Limitations: The Market Adjusted Model assumes homogeneous firm risk, sector-level comparative analysis was not conducted, and domestic macroeconomic variables were not controlled for. Contribution: This study provides novel multisector evidence on how an emerging market responds to unilateral trade protectionism, contributing to the literature on event studies, signaling theory, and trade policy reactions.